南極リュツォ・ホルム湾昭和基地周辺海域における海氷変動と生物過程の関係(シンポジウム:世界の沿岸海域における環境と生態系の長期変動) - 小達, 恒夫; Odate, Tsuneo (日本海洋学会, 2005)
リュツォ・ホルム湾昭和基地(南緯69度00分,東経39度35分)周辺における夏季のクロロフィルa濃度の変動と海氷分布を,既存の観測結果を基に比較した.1991/92年夏季には,氷厚が薄い地点(2m)でのみクロロフィルa濃度の大きな上昇が1月中旬に見られ,氷厚が厚い地点(2.5〜2.7m)では上昇の度合いが小さかった.1996/97年夏季には,氷厚が2.1〜3.6mの地点で観測を行ったが,クロロフィルa濃度に地点間の違いは認められず,いずれの地点においても1月下旬にかけて最高濃度となった.1997/98年夏季の観測点(氷厚;2.2〜2.6m)では,12月下旬に1回目の上昇が,1月中旬に2回目の上昇が観測された.定着氷の北限は,1991/92年夏季にはほぼ南緯68度付近にあったが,1996/97年夏季にはほぼ南緯68度45分付近まで南下していた.更に1997/98年夏季には,12月中旬に既に南緯69度付近まで退行していた.氷縁ブルームが起こっている定着氷縁と観測海域の距離が,クロロフィルa濃度の年変動に違いをもたらしていると推察された. Variations in the chlorophyll a concentration (Chl a) near Syowa Station (69°00'S,39°35'E) in Lutzow-Holm Bay over three summers were compared with the fast ice distribution. During the summer of 1991/92, a large increase in the Chl a occurred under light sea ice conditions (2m) in mid January, and a lower increase under heavy sea ice conditions (2.5-2.7m). During the summer of 1996/97, a uniform increase in Chl a was observed, reaching a maximum in late January, although the sea ice thickness varied during this time (2.1-3.6m). In late December 1997, the first increase in Chl a occurred under a sea ice thickness of 2.2-2.6m. The Chl a decreased during the period from the 8^ to the 14^ of January and increased again after the 15^ of January. From mid December to mid January 1991/92, the northern fast ice limit was located at approximately 68°S. In the 1996/97 summer season, the northern fast ice limit was located at approximately 68°45'S at the end of December and the beginning of January. In mid December 1997, the northern limit was already located south of 69°S. The spatial relationships between the position of the ice edge, where the ice edge bloom occurs, and the survey area seem to result in the annual variation in Chl a near Syowa Station. journal article